Elmidae Curtis, 1830 (Coleoptera, Polyphaga, Byrrhoidea) of the Neotropical region - Segura, Melissa Ottoboni; Dos Passos, Maria Ines Da Silva; Fonseca-Gessner, Alaíde Aparecida; Froehlich, Claudio Gilberto (Zootaxa, 2013)
A bibliography of significant taxonomic papers on Elmidae (Coleoptera, Polyphaga, Byrrhoidea), and a checklist of valid species and subspecies and their geographic distributions are provided. Forty-seven genera and 430 valid species are included. Maps show the geographic distribution of the genera by country.